Related aspects of aerobic training optimization for high performance - Oliveira, M. F. M.; Caputo, F.; Greco, C. C.; Denadai, B. S. (Revista Brasileira de Medicina do Esporte, 2010)
The objective of this work was to present recommendations aiming the aerobic training optimization, from the knowledge of the indexes of functional fitness and their physiological mechanisms. Concerning highly trained athletes, the accuracy in training elaboration can be the safest way to improve aerobic performance, since for these individuals, it is normal that the training load is changeable between an insufficient stimulus and the overtraining syndrome symptoms onset. Therefore, there are several factors that should be taken into account for the elaboration of a training program. The knowledge on fatigue mechanisms and physiological responses at different exercise intensities and durations is essential for the correct training session elaboration. Moreover, high-intensity interval training is indispensable to improve performance in highly trained athletes; however, it should be performed only after adequate recovery period. Thus, a good relationship between coach and athlete is also important for planning suitable recovery periods prior to excessive fatigue. The coach should keep accurate records of training loads and recovery times, learning hence the kinds of loads that can be individually tolerated. Among the important factors that can affect aerobic performance during competition and should be considered, we can name appropriate warm-up planning and adverse environmental conditions. After collecting all this information, it is possible to elaborate the training bases (frequency, volume, intensity and recovery) aiming at progressive improvement of aerobic performance.